REALITAS SIMBOL KEISLAMAN DALAM FILM TELEVISI ISLAMIC SYMBOLIZATION REALITY ON TELEVISION FILM - Hermawan, Herry (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2009)
This research is concerned to present an analysis of Islamic symbolization in the context of a theory of social construction of reality as a dialectical process consist of three moments or step, externalization. objectification and internalization. Through the qualitative research method. the analysis techniques in use were genre and narrative analysis, semiotics analysis and hermeneutics analysis. The result of this research showed that Islamic symbolization reality whether it is constructed by society or liy television film derive from the paramount realities of interaction between religion. culture and economy. The result of research also showed that capitalism is a dominant ideologv in which stand up behind the text of Islamic svmbolization television film.